Gravure printing for three subsequent solar cell layers of inverted structures on flexible substrates - Voigt, Monika M.; MacKenzie, Roderick C. I.; Yau, Chin P.; Atienzar, Pedro; Dane, Justin; Keivanidis, Panagiotis E.; Bradley, Donal D.C.; Nelson, Jenny (My University, 2011)
Inverted organic photovoltaic devices have been fabricated by gravure printing on a flexible substrate. In order to enable printing of multiple layers sequentially, a systematic study of wetting behaviour of each layer in the device is performed. Successful wetting of a hydrophobic P3HT:PCBM surface by a hydrophilic PEDOT:PSS ink is achieved with the addition of a surfactant/alcohol to the PEDOT:PSS ink and with oxygen plasma treatment. We are therefore able to print titanium oxide, poly(3-hexylthiophene) (P3HT) blended with [6,6]-phenyl C61 butyric acid methyl ester (PCBM) and poly-3,4-ethylenedioxythiophene: poly(styrene sulphonic acid) (PEDOT:PSS). As result we get for three printed layers a 0.6% power conversion efficiency. © 2010 Elsevier B.V. All rights reserved.
Keywords: Gravure; Inverted structures; Organic solar cells; P3HT:PCBM; Printing; Wetting behaviour